O tempo e as histórias de vida: contribuições para a pesquisa interdisciplinar - Casadei, Silmara Rascalha (2014)
This paper aims to present contributions to interdisciplinary research from studies and reflections on life stories and their relationship to interdisciplinarity in order to understand the degree of importance of their insertions in research processes. Using a metaphor of the butterfly metamorphosis , the route will be used in the methodology itself to unveil the history of literary life and teaching of the author of this thesis , showing that behind each search , there is the world of the researcher , which often gets locked in his cocoon of external studies did not allow time to investigate internally and not to make known . The study also reflects on the use of time in the movements of humanity performing a flight on the concepts of time in the western world , from Greek mythology to the present day , understanding that it is essential we analyze the temporal contexts which we operate to meet the opportunities and gaps of light that allow us to envision new times for personal and professional development . The survey will cover mainly the historical panorama of life histories in the academies , through a literature review that will dialogue with the possibilities of interdisciplinary activities in conjunction with FAZENDA , PIENAU , JOSSO , FREIRE , DE LA TORRE , ESPÍRITO SANTO , leading theorists and presented with the works of CASADEI ( author of this thesis ) . To discuss and propose the relationship between interdisciplinarity , personal history , life history in academies and resizing the use of time , the study The study proposes that it is of fundamental importance to the entrance of life stories , not only in universities but in all levels of education , which will allow more real , whole and humane approaches , because being who saw themselves more clearly see each other and when they met , they may look at the world in an interdisciplinary way to work with the best proposals for the well collective. The thesis concludes that it is necessary to reconfigure the schools and universities as spaces not only intellectual, but also existential , thus becoming little islands of peace , centers pollination of life